2017
DOI: 10.2147/vhrm.s125966
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic fitness is associated with low cardiovascular disease risk: the impact of lifestyle on early risk factors for atherosclerosis in young healthy Swedish individuals – the Lifestyle, Biomarker, and Atherosclerosis study

Abstract: BackgroundThe progression of cardiovascular disease (CVD) and atherosclerosis is slow and develops over decades. In the cross-sectional Swedish Lifestyle, Biomarker, and Atherosclerosis study, 834 young, self-reported healthy adults aged 18.0–25.9 years have been studied to identify early risk factors for atherosclerosis.PurposeThe aims of this study were to 1) assess selected cardiometabolic biomarkers, carotid intima–media thickness (cIMT) as a marker of subclinical atherosclerosis, and lifestyle-related ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 29 publications
3
54
0
3
Order By: Relevance
“…None of the subjects were smokers and as expected we observed that aerobic fitness was associated with reduced risk to develop CVD in the future. We also observed that subjects with high aerobic fitness had lower HOMA-IR as compared to less well-trained subjects participating in the study [7].…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…None of the subjects were smokers and as expected we observed that aerobic fitness was associated with reduced risk to develop CVD in the future. We also observed that subjects with high aerobic fitness had lower HOMA-IR as compared to less well-trained subjects participating in the study [7].…”
Section: Introductionsupporting
confidence: 60%
“…The previously published test score [7] was based on the total response of the questionnaire and presented automatically after the test to the participants as a score from 1 to 12 points. In connection, the participants also received advices on how to improve their diet.…”
Section: Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice subjected to resveratrol supplement and anaerobic training are associated with elevated tissue glycogen, muscle growth, and aerobic capacity (Kan et al, ). In a clinical study, a higher aerobic fitness correlates with lower CVD risk (Fernström, Fernberg, Eliason, & Hurtig‐Wennlof, ).…”
Section: Molecular Basis Of Resveratrol Actionmentioning
confidence: 99%